Design and Evaluation of Packaging Art Based on Sentimental Value Calculation and Clustering - Wu, Fang; Alatas, Bilal (Igi Global, 2024)
This paper introduces the cultural dimension of product packaging, elucidates the quantification principle and methodology governing customer aesthetic experiences, propounds an innovative packaging style design approach, and presents an evaluation model based on an enhanced neural network. Using tea packaging design as an illustrative case, the methodology initially aligns adjectives, subsequently computes the emotional depth value, and ultimately derives the corresponding correlation between customer emotional experiences and design elements through a neural network. Subsequently, the designed model is validated using tea packaging design as a practical example. The outcomes demonstrate the model's accuracy and efficacy in establishing the mapping between design elements and aesthetic experiences, offering novel insights for the evolution of packaging design in the contemporary market landscape.
Keywords: Packaging Design; Aesthetic Experience; Emotional Value; Neural Network; Design Element; Modern Market; Quantification Principle; Tea